On the Interrelation between Cognitive and Emotional Minds in Speech - Paronyan, Shushanik; Rostomyan, Anna (Armenian Folia Anglistika, 2011)
The present article investigates the interrelation between cognitive and emotional expressions in human mind, as well as the characteristics of their verbal and non-verbal expressions in modern English discourse. Cognitive and pragmatic concepts have been applied to carry out the analysis of the factual material. The role of emotions in the process of speech creation and perception is paid special attention to. The latter are viewed not only as emotional phenomena, but also as components of fundamental knowledge which highly affect the cognitive system of speech.